Diversity and Siderophore Production of Actinomycetes from Eastern Thai Coastal Marine Sediments - Pornpan Ruttanasutja (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Four sediment samples from Rayong Province, Thailand were examined for actinomycete diversity by culture independent method. DNA library was constructed using actinomycete specific primers. A total of 153 non chrimeric clones were analyzed. All clones were affiliated in the Class Actinobacteria covering 4 subclasses, 4 orders, 9 suborders, 23 families and 39 genera. Dominant actinomycete groups in all 4 samples were members of the genus Illumatobacter in the family Acidimicrobiaceae and genus Iamia in the family Iamiaceae. The highest actinomycete diversity in term of species richness and distribution was found in the sediment from Klong–Ta–Guan with Chao's value of 343 ribotypes at species level, Shanon Wiener and Simpson index of 3.76 and 0.26, respectively. Ninety clone sequences (58%) showed less than 97% 16S rRNA similarity to any known actinomycete culture and may represent novel species. These findings suggest that the diversity of actinomycetes in Thai coastal sediments is high and large numbers of actinomycetes remains to be characterized by cultivation for bioprospecting. An improved isolation method for actinomycetes from coastal marine sediments was developed. Four pretreatments, 3 enrichment broths and 15 selective media were tested for isolation using sediment sample from Klong–Ta–Guan. Pretreatment methods were (1) preparation of soil suspension by tenfold dilution and shaking 10-1 dilution of sediment suspension at 125 rpm for 10 minutes (2) 1.5% phenol treatment (3) shaking sediment suspension (1 g: 3 ml) at 125 rpm for 10 minutes and (4) shaking sediment suspension (1 g: 3 ml) at 125 rpm for 60 minutes. Three enrichment broths were (1) Marine Broth (MB) (2) Soil Extract Solution (SES) and (3) Marine Soil Extract Broth (MSB). All isolation plates from 15 selective media were incubated at 25oC for 30 days. Actinomycetes were isolated only from pretreatment (4). Marine broth was found to promote the isolation of actinomycetes with high ratio of total bacteria : actinomycetes (2:1). In general, diluted media or low nutrient media were more effective in the isolation of actinomycetes. A total of 209 isolates of actinomycetes were obtained with colony count ranging from 0–747 cfu/g. Molecular identification based on 16S rRNA gene sequencing revealed that these isolates belonged to 8 genera, namely Curtobacterium, Dermacoccus, Micromonospora, Microbispora, Pseudonocardia, Rhodococcus, Streptomyces and Tsukamurella. However, results from culture dependent and culture independent studies of Klong-Ta-Guan sediment, showed only 3 overlap genera, namely Micromonospora, Rhodococcus and Streptomyces. This isolation method was then used to isolate actinomycetes from other 7 sediment samples. In total, 529 isolates were obtained from all sediment samples and were identified to members of 3 genera: Micromonospora, Rhodococcus and Streptomyces. These results showed the highest diversity in Klong–Ta–Guan sample which were in agreement with the results from culture independent study. The study on 7 basal media for Chrome azurol S (CAS) assay which used for prescreening of siderophore production, indicated that Modified King B Agar (MKBA) (pH 7.0) was the most suitable media for actinomycete growth and siderophore production. A total of 738 isolates were screened for siderophore production by CASMKBA (pH 7.0) based medium and all of them produced siderophore. Seventy–nine isolates of Pseudonocardia and Streptomyces which showed large orange halo zone were selected for determination of type and quantity of produced siderophore by ferric perchlorate assay for hydroxamate type and Arnow’s assay for catecholate type. All actinomycete isolates produced hydroxamates type siderophore with more than half (69.62%) produced both hydroxamate and catecholate types. Streptomyces sp R1-2A/J806 from Klong–Ta–Guan sample showed the highest yield of 2.03 nmol/l and 0.81 mmol/l for hydroxamate and catecholate types, respectively. The type of siderophore was confirmed by thin layer chromatography which showed similar results with screening in both agar plate and culture broth. Time course study of siderophore production from actinomycetes was carried out using isolates R1–2B/D805 and R1–2B/N205, the highest hydroxamate and catecholate producer, respectively. Actinomycetes were cultured in MKB broth (pH 7.0) and growth and siderophore production were measured. It was found that actinomycetes produced highest siderophore during late log phase or early stationary phase. Each type of siderophore was produced in different growth period. Siderophore producing genes were detected using desD gene for hydroxamate type and entF gene for catecholate type. All of 79 isolates were detected with desD gene which encode desferrioxamine. Comparison of sequence data showed that these desD genes were closely related to desD genes in various Streptomyces sp. Furthermore, the entF gene which encodes for enterobactin was not found in all the 55 catecholate producing isolates. This observation suggested that these isolates may contain catecholate type genes other than enterobactin. All siderophore producing actinomyctes were tested for their antibacterial activity against three bacterial pathogens; Aeromonas hydrophila, Pseudomonas fluorescens and Vibrio parahaemolyticus by agar well diffusion method on MKBA (pH 7.0), which supported siderophore production and Modified King B Iron Agar (MKBIA) (pH 7.0), which inhibited siderophore production. The antifungal activity was tested with two fungal pathogens; Colletotrichum gloeosporioides and Fusarium oxysporum by dual culture method on CAS–MKBA (pH 7.0) and CAS–MKBIA (pH 7.0). A total of 24 isolates (3.25%) showed antibacterial activity against at least one tested pathogenic bacterium and only 7 isolates (0.95%) inhibited all pathogenic bacteria. Seventy-nine isolates (10.70%) showed growth inhibitory activity against all pathogenic fungi, isolate R8-K310 from Had-Sai-Thong sediment showed the highest inhibition of 59% and 61% for C. gloeosporioides and 57% and 53% for F. oxysporum on CAS–MKBA (pH 7.0) and CAS–MKBIA (pH 7.0), respectively. Both antibacterial and antifungal activities of actinomycetes on MKBA (pH 7.0) and MKBIA (pH 7.0), did not show any statistically difference (P<0.05). This result suggested that the antagonistic activity was not related to siderophore production but may be due to the inhibitory effect of other secondary metabolites.